Analisis Pendapatan Petani dan Faktor-Faktor Yang Mempengaruhi Produktivitas Sayur Mayur di Kecamatan Purba Kabupaten Simalungun - Mega Fajri Aini Saragih; Hasnudi Hasnudi; Teguh Wahyono (JURNAL AGRICA, 2018)
The Purba District is the largest central areas of vegetable production and is one of the local areas in the development of vegetable crops at Simalungun Regency.  This research uses field observations by the questionnaire and interview research instruments, this research is descriptive quantitative. The population were all the tomatoes, cabbage and potatoes farmers at 3 (three) sample villages at the Purba District. The respondents were 70 people farmer scattered samples at Nagori Tiga Runggu, Pematang Purba and Hutaraja. Data collected by interview, questionnaire, and study documentation. The data analysis used the multiple linear regression analysis estimated by the Cobb - Douglas production function. The results shows that the variable cropping patterns and organic fertilizers and pesticides had a signficantly effect on land productivity of vegetables farming. Then the chemical fertilizers and labour variables had a non significantly effect on the land productivity of vegetables farming at Purba District of Simalungun Regency. By this study had been conclusion that the vegetables productivity of vegetable farming highest obtained at the cropping pattern of land planted with cabbage 3 times in 1 year. The productivity by 59.988,98 kg/ha/year. The highest revenue for vegetable farmers on cropping pattern obtained 5 where the land planted with tomatoes and potatoes 1 times in a year. The income average of Rp. 100.895.515,7/Ha/year. Keywords : productivity, production, vegetables, Cobb-Douglas